Pembentukan Karakter Siswa melalui Kegiatan Ekstrakurikuler Pendidikan Agama Islam di MTs Negeri 4 Mandailing Natal - Karnada Nasution (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Character education is an important issue nowadays. This is due to the occurrence of moral degradation among adolescents, especially among students, which are increasingly apprehensive. The moral degradation that occurs can be seen in the character of students who lack discipline, do not respect teachers, cases of bullying, and even pornography. This study aims to analyze the implementation of Islamic religious education extracurricular activities at MT's Negeri 4 Mandailing Natal, analyze the values of character education, and analyze the impact of Islamic religious education extracurricular activities in shaping the character of MT's Negeri 4 Mandailing Natal students. This study used a qualitative research approach using descriptive methods. Data were obtained through observation, documentation, and interviews with selected informants with purposive sampling. The research findings are as follows: PAI extracurricular activities such as Tahfidz Al- Qur'an, Congregational Duha Prayers, Congregational Zuhur Prayers, Yasinan, calligraphy, and others. The purpose of carrying out these activities is to foster and develop the cognitive, affective, and psychomotor aspects of students under the PAI extracurricular guidelines issued by the Directorate of Islamic Religious Education and the Ministry of Religion. Character education values formed through PAI extracurricular activities such as religious, disciplined, peace-loving, responsible, social care, and honesty. The conclusion is that the implementation of PAI extracurricular activities both directly and indirectly can have a positive impact on shaping student character and these activities need to be carried out repeatedly and continuously.